Two-path succesive relaying schemes in the presence of inter-relay interference - Liau, Qian Yu (2016)
Relaying is a promising technique to improve wireless network performance. A conventional relay transmits and receives signals in two orthogonal channels due to half duplex constraint of wireless network. This results in inefficient use of spectral resources. Two-Path Successive Relaying (TPSR) has been proposed to recover loss in spectral efficiency. However, the performance of TPSR is degraded by Inter-Relay Interference (IRI). This thesis investigates the performance of TPSR affected by IRI and proposes several schemes to improve relaying reliability, throughput and secrecy. Simulations revealed that the existing TPSR could perform worse than the conventional Half Duplex Relaying (HDR) scheme. Opportunistic TPSR schemes are proposed to improve the capacity performance. Several relay pair selection criteria are developed to ensure the selection of the best performing relay pair. Adaptive schemes which dynamically switch between TPSR and conventional HDR are proposed to further improve the performance. Simulation and analytical results show that the proposed schemes can achieve up to 45% ergodic capacity improvement and lower outage probability compared to baseline schemes, while achieving the maximum diversity and multiplexing tradeoff of the multi-input single-output channel. In addition, this thesis proposes secrecy TPSR schemes to protect secrecy of wireless transmission from eavesdropper. The use of two relays in the proposed schemes deliver more robust secrecy transmission while the use of scheduled jamming signals improves secrecy rate. Simulation and analytical results reveal that the proposed schemes can achieve up to 62% ergodic secrecy capacity improvement and quadratically lower intercept and secrecy outage probabilities if compared to existing schemes. Overall, this thesis demonstrates that the proposed TPSR schemes are able to deliver performance improvement in terms of throughput, reliability and secrecy in the presence of IRI.